Peran Mediator Hubungan Industrial Disnakertrans Kota Serang Dalam Penyelesaian Kasus-Kasus Perselisihan Hubungan Industrial - Rina Yulianti (Jurnal Administrasi Publik, 2013)
In industrial relations, there could be a dispute between workers and employers(companies). Law no. 2 of 2004 concerning the proposed already complete set,following the steps of the mediation process and the documents required. So themediator's role is very important in helping to resolve the dispute. Disputes oftendetrimental to workers in obtaining their rights, they often ask for helpDisnakertrasns Serang in resolving cases they face. Disnakertrans should be ableto face the challenges in the future related to frequent disputes. In this study,researchers conducted interviews, to find out more in depth how the role of themediator can perform its duties and functions well.